Bridging Information, Institutions, and Livelihoods: A Systematic Review of Climate-Smart Agriculture Adoption and Food Security among Smallholders - Nathanael, Farrel Yoel; Muhammad Aledeh; Atkinson, Christopher L.; Sizyoongo Munenge; Elena Ivanovna Dorokhova (Perencanaan Wilayah dan Kota FT UB, 2026)
Climate-Smart Agriculture (CSA) is widely promoted to strengthen smallholder resilience and food security under climate change, yet evidence on why adoption produces uneven outcomes remains fragmented. This systematic literature review, guided by PRISMA-2020, synthesizes 58 Scopus-indexed empirical studies published between 2021 and 2025 to examine how climate information, institutional mediation, livelihood assets, and equity conditions interact in shaping CSA adoption and food-security outcomes. Rather than treating these dimensions separately, the review develops an information–institution–livelihood analytical framework that links access to climate knowledge, trust-based institutional support, household asset portfolios, and socially differentiated participation. Evidence was analyzed through thematic synthesis, comparative synthesis, evidence mapping, and study-quality appraisal, without claiming formal meta-analysis. The findings show that localized climate information improves preparedness and adoption only when mediated by credible extension systems, cooperatives, credit access, and secure land or resource rights. Livelihood diversification and bundled CSA practices generally strengthen income stability, resilience, and food security, but their effects vary across agroecological zones, commodities, and institutional contexts. Reported quantitative outcomes, including 7–9% higher food-security likelihood in Niger and an LVI score of 0.49 in Ethiopia, are interpreted as study-specific estimates rather than pooled effects. Gendered access to land, finance, information, and farmer organizations emerges as a central mechanism shaping adoption intensity and resilience. The review contributes by clarifying that CSA effectiveness depends on coordinated knowledge systems, accountable institutions, diversified livelihood assets, and equity-sensitive governance, rather than on technology dissemination alone.